Implementation of Zis (Zakat, Infaq, Sedekah) with Corporate Social Responsibility (Csr) in an Effort to Support the Sdgs Program (Case Study: Point 1 No Poverty) - Yuliarthi, Ni Wayan; Supiani, Nia; Hasanah , Uswatun; Saputra, Muhamad Fajar (Journal of Finance and Business Digital, 2024)
This research analyzes the integration of Zakat, Infaq, and Sadaqah (ZIS) into Corporate Social Responsibility (CSR) programs to support the Sustainable Development Goals (SDGs), particularly poverty alleviation (No Poverty). Using a qualitative approach, case studies of companies implementing ZIS in CSR programs were conducted through interviews and document analysis. Findings reveal various ZIS applications, including scholarships, business capital assistance, and financial management counseling for the underprivileged. The implementation of ZIS in CSR programs benefits recipients, creates jobs, enhances education, and boosts local economies. Collaboration between companies, zakat institutions, and the government plays a crucial role in maximizing impact. The study underscores the strategic importance of integrating ZIS into CSR programs to achieve sustainable development goals, particularly in poverty reduction efforts in Indonesia.